HOW BRAND TRUST, GREEN MARKETING AND ONLINE CUSTOMER REVIEWS INFLUENCE PURCHASE DECISIONS: THE MODERATING ROLE OF PERCEIVED RISK - Resita Mila Vinata; Lestari Wuryanti; Ayu Nursari (PT. ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of Brand Trust, Green Marketing, and Online Customer Review on Purchase Decision with Perceived Risk as a moderating variable in florist businesses in Bandar Lampung. The increasing development of digital marketing and consumer awareness regarding service quality and environmental issues have encouraged florist businesses to improve their marketing strategies in order to attract consumers and increase purchasing decisions. This research used a quantitative approach with data collected through questionnaires distributed online and offline to 113 respondents who had purchased products from florist businesses in Bandar Lampung. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS Statistics 23. The results showed that Brand Trust, Green Marketing, and Online Customer Review had positive and significant effects on Purchase Decision, both partially and simultaneously. Online Customer Review was identified as the most dominant variable influencing Purchase Decision. However, Perceived Risk was not proven to moderate the relationships between Brand Trust, Green Marketing, and Online Customer Review on Purchase Decision. The findings indicate that consumers rely more on trust, customer experiences, and online reviews rather than perceived uncertainty when making purchasing decisions in florist businesses. This study contributes to the development of consumer behavior and digital marketing literature, particularly in creative service industries such as florist businesses.